The social complaint from the infant gaze: Bad Hair by Mariana Rondón - Polo Pacheco, Gilberto; De Rugeriis, Romina (situArte, 2021)
With the purpose of analize the film Bad Hair (2013) by Mariana Rondón, this qualitative study of a descriptive type is addressed in the children's universe through a boy who wants to straighten his hair, whose unprejudiced mind has no problems, but triggers the screams of an intolerance in their hostile environment. Breaking the structure of his old production where the game was the key, Rondón displays the human being's gaze that is contrasted with his fears and castrations, conditioned to the pre-established social foundations, theoretically based on Dudley (1993), Münsterberg (1916), Sulbarán (2000) and García de Molero (2007). Methodologically, open interviews and bibliographic-documentary review were used. Finally, the strategies used by this author to show the struggle of an infant who wants to be free, and to be able to fulfill his dream, encountering a wall imposed by a society darkened with castrating foundations, are exposed.